ANÁLISE DAS DIRETRIZES CURRICULARES DA EDUCAÇÃO BÁSICA DO PARANÁ – CIÊNCIAS (2004-2008) - Caldas, Luiz Américo Menezes (2016)
This research analysed the construction process of the Basic Education Curriculum Guidelines (DCE - Diretrizes Curriculares para a Educação Básica) of the Education State Department of Paraná (abbreviated SEED/PR), developed from 2003 to 2008, with particular reference to the Curriculum Guidelines for teaching Science. The theoretical framework is based on the ideas of Michael Apple, Gimeno Sacristán and other authors in the curriculum area. The research objectives were: a) describe the construction process of the Basic Education Curriculum Guidelines of the State of Paraná, with particular eference to the Science Guidelines; b) identify the foundations and theoretical conceptions of the DCE of Science; and c) analyze the perceptions of Science teachers and educators on the DCE and the possibilities of its implementation in the context of practice. The research involved the following data collection procedures: a) document analysis; b) interviews with seven teachers and three educators from three state schools in the city of Ponta Grossa - Paraná; and c) interview with a former member of the technical-pedagogical staff from the Science area (SEED) and with the coordinator of Science from the Regional Center of Education of Ponta Grossa - Paraná. The main conclusions indicate that: a) the participatory construction of DCE marked the resumption of the main role of SEED/PR in the definition of a common curriculum for the State School Network; b)the curricular proposal for teaching Science constitutes an innovative proposal in relation to the traditional perspective of teaching Science; c) from 2011, with the change in the state government management, the actions for the realization of the DCE have become episodic, hindering their consolidation; d) the teachers use the DCE for the preparation of the Teacher Work Plan, but in practice they find it difficult to develop the DCE proposals.